Perbedaan Tingkat Pengetahuan Tentang Pemanis Buatan Dalam Makanan Sebelum Dan Sesudah Mendapat Leaflet Pada Penjual Jajanan Di SD Kabupaten Klaten - Septiawan, Agung Firman, Arifah Sri Wahyuni, M.Sc., Apt, Trisharyanti DK, M.Farm., Apt (2016)
Artificial sweeteners in everyday life must be considered, because it is very influential in health. Artificial sweeteners actually not prohibited but there are certain limitations in its use, therefore, this study aimed to improve the knowledge about artificial sweeteners of seller by using leaflets. The purpose of this study was to measure the level of knowledge in elementary school vending X district before and after receiving education in the form of leaflets. This research includes studies using experimental design pretest-posttest design. Sampling using cluster random sampling with a sample size of 100 respondents. This research using instruments such as questionnaires and leaflets. Data were analyzed using t-test (paired t-test). This study shows the results of the average value of the respondents 'knowledge before granting leaflet of 35.14 ± 8.00 were categorized as low and after giving leaflets respondents' knowledge increased with an average value of 69.89 ± 8.02 were included in the medium category. It can be concluded there is a difference between knowledge before and after the delivery of leaflets about artificial sweeteners that can be seen from the test results significantly p <0.05.